2020
DOI: 10.1089/hum.2019.149
|View full text |Cite
|
Sign up to set email alerts
|

Adult and Cord Blood-Derived High-Affinity gB-CAR-T Cells Effectively React Against Human Cytomegalovirus Infections

Abstract: Human cytomegalovirus (HCMV) reactivations are associated with lower overall survival after transplantations. Adoptive transfer of HCMV-reactive expanded or selected T cells can be applied as a compassionate use, but requires that the human leukocyte antigen-matched donor provides memory cells against HCMV. To overcome this, we developed engineered T cells expressing chimeric antigen receptors (CARs) targeted against the HCMV glycoprotein B (gB) expressed upon viral reactivation. Single-chain variable fragment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 49 publications
1
28
0
Order By: Relevance
“…It would be interesting to evaluate if reactive T cells directed against lytic-or latency-associated antigens could be generated. In fact, using humanized mice infected with HCMV at 17-19 weeks after HCT, we recently showed therapeutic effects of adoptive T cells expressing an engineered chimeric antigen receptor targeting gb (gB-CAR-T) administered 8 weeks later [46].…”
Section: Plos Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…It would be interesting to evaluate if reactive T cells directed against lytic-or latency-associated antigens could be generated. In fact, using humanized mice infected with HCMV at 17-19 weeks after HCT, we recently showed therapeutic effects of adoptive T cells expressing an engineered chimeric antigen receptor targeting gb (gB-CAR-T) administered 8 weeks later [46].…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Mutagenesis was performed to change the fusion loop residues and avoid protein aggregation by modifying the YAYIH 154-158 and GSTWLY 238-243 residues into EEEEE and EEEEEE, respectively. Generation of the S2 cell lines secreting the gB ectodomains and the protein production were performed as described 46 . The recombinant gB ectodomains were purified from the supernatant by affinity chromatography using StrepTactin resin (IBA Biosciences, Göttingen, Germany), dialyzed into PBS and used as such for the experiments.…”
Section: Gb Protein Productionmentioning
confidence: 99%
“…Expression of gp350CARs on T cells was compared with gBCAR, recognizing the glycoprotein gB of HCMV and generated with the same vector backbone and signaling domains. 29 The mean fluorescence intensities of the different CAR + T cells were calculated (see flow cytometry gating strategy in Figures S2 B and S2C). The reference gBCAR showed significantly higher expression on the surface of CD4 + and CD8 + T cells than 7A1-gp350CAR (p ≤ 0.01) and 6G4-gp350CAR (p ≤ 0.001) ( Figures 1 C and 1D; Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a recent related study, we have shown that CB-derived CAR-T cells targeted against the HCMV gB envelope also showed efficacy in vitro and in vivo . 29 Therefore, similar to VST cells expanded with peptides and targeted against several viruses, polyfunctional CAR-T cells targeted simultaneously against EBV and HCMV can be developed in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation